Infratemporal fibrolipoma in a 9-year-old female patient - Kowalczyk, Robert; Żabski, Tomasz; Sagan, Leszek; Zabielska, Paulina; Karakiewicz, Beata (Family Medicine & Primary Care Review, 2020)
Fibrolipoma (FL) is a rare subtype of a benign neoplasm as of lipoma, as well as being rarely present in the maxillo-facial area. The reported case is a significant cause for the natural history description of FL development in skull base in childhood. The authors report the case of a female patient, aged 9. In the case reported by us, during a 5-year observation, a disturbed development of maxillary sinus adjacent directly to the change occurred. In addition, after the surgery, orthodontic disturbances developed. Such a course may plead in favour for the necessity of an earlier decision on surgical treatment. Our report is a significant contribution to knowledge of the natural history of FL development in skull base in childhood. It shows that growth of the tumour, though very slow, is progressive and changes regional anatomy and function. Therefore, after the primary diagnosis of FL, surgical treatment without a long follow-up should be strongly considered.